Evaluation of domino liver transplantations in Germany. (14th May 2013) - Bolte, Fabian Johannes; Schmidt, Hartmut H.‐J.; Becker, Thomas; Braun, Felix; Pascher, Andreas; Klempnauer, Jürgen; Schmidt, Jan; Nadalin, Silvio; Otto, Gerd; Barreiros, Ana Paula
Summary A retrospective multicenter study has been conducted to evaluate domino liver transplantations (DLTs) in Germany. The study provides insight into survival and features having an impact on the assessment of neuropathy after DLT. In addition, a neurologic follow‐up program with a scheme to estimate the likelihood of de novo amyloidosis is presented. A series of 61 DLTs at seven transplant centers in Germany was enrolled. The mean age of domino recipients at the time of transplantation was 58 years, 46 of them being men, and 15 being women. The median follow‐up was 46 months. The overall 1‐, 3‐, and 5‐year survival of domino recipients was 81.6%, 70.8% and 68.8%, respectively. Causes of death were primarily not related to familial amyloidosis. The main indication of DLT was hepatocellular carcinoma. Two of the reported domino recipients developed symptoms and signs of de novo amyloidosis within 10 years after transplantation. A total of 30 domino graft recipients (49.18%) presented with diabetes post transplantation. In conclusion, an advanced follow‐up program is crucial to evaluate the risk of transmitting familial amyloidosis by DLT and to establish more strict selection criteria for domino recipients.